9-4(5x-7)=

Simple and best practice solution for 9-4(5x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-4(5x-7)= equation:


Simplifying
9 + -4(5x + -7) = 0

Reorder the terms:
9 + -4(-7 + 5x) = 0
9 + (-7 * -4 + 5x * -4) = 0
9 + (28 + -20x) = 0

Combine like terms: 9 + 28 = 37
37 + -20x = 0

Solving
37 + -20x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-37' to each side of the equation.
37 + -37 + -20x = 0 + -37

Combine like terms: 37 + -37 = 0
0 + -20x = 0 + -37
-20x = 0 + -37

Combine like terms: 0 + -37 = -37
-20x = -37

Divide each side by '-20'.
x = 1.85

Simplifying
x = 1.85

See similar equations:

| x^2+118x-378=0 | | -6x^2+2+11x^2-13-5x= | | 13-52+f=34 | | 6x-1=3y+2 | | 5(c+9)=5(c-4) | | 2(1/3)x3(2/7) | | r^2-3r=2r+14 | | 2lne+3ln(x-1)=5 | | 5y-3+y+41=6y+40-2 | | 9x^2-14x-4+3x= | | x^-2=9/16 | | 24a/4 | | 19x-3=14+2x | | x^*2=9/16 | | 24a/4= | | Y=-6+3x+x^2 | | (3y+1)=23+23 | | 4xy^2z/8x^2y-4xy^2 | | 4=6-y | | -m^2+7m=0 | | [-6x-(3x+3)]=-4-[4(2x-3)-3x] | | 1.93+0.670= | | 25k^2=64 | | x^4+5=3 | | 0.25x^2+1.5x-2=0 | | x6/5=x/7 | | 6y^2+17y-28=0 | | 3s-25=-43+5s | | a^2+8a+29=12 | | 10+11c+c^2=0 | | 22/18=99/t | | -10(43)+0.35x=0.05(x-2) |

Equations solver categories